Biomimetic materials: a promising strategy for periodontal tissue engineering and regeneration - Zhang, Qinghua; Gou, Ce; Zhang, Zhijun (Frontiers in Bioengineering and Biotechnology, 2025)
Periodontitis is a chronic inflammatory disorder that causes irreversible damage to periodontal tissues, such as the alveolar bone, cementum, and periodontal ligament. Clinical treatments for periodontitis include non-surgical and surgical approaches, complemented by the utilization of various biomimetic materials to repair damaged tissues, a process known as periodontal tissue regeneration. Biomimetic materials have demonstrated extensive application prospects in periodontal tissue regeneration owing to their outstanding biocompatibility, controllable mechanical properties, and biomimetic microstructures. This review begins by delineating the cells used in periodontal tissue regeneration and summarizes the applications and research hot spots of commonly employed biomaterials in periodontal tissues. This further highlights the advantages of using biomimetic materials as bone substitutes, barrier membranes, and complex scaffold-manufacturing techniques. In addition, an in-depth discussion is conducted on their biological safety and physical properties. Moreover, this article summarizes the research advancements of extracellular matrix (ECM) materials in periodontal tissues, which hold great promise as highly prospective biomaterials for periodontal tissue regeneration. Finally, this article provides a comprehensive summary of the current limitations and challenges associated with the application of biomaterials in periodontal tissue regeneration. Although biomimetic materials still encounter challenges regarding stability and long-term efficacy during clinical translation, this review offers insights into the basic research and clinical treatment of periodontal regeneration.